2022
DOI: 10.1021/acsnano.1c09465
|View full text |Cite
|
Sign up to set email alerts
|

Twist-Stabilized, Coiled Carbon Nanotube Yarns with Enhanced Capacitance

Abstract: Coil-structured carbon nanotube (CNT) yarns have recently attracted considerable attention. However, structural instability due to heavy twist insertion, and inherent hydrophobicity restrict its wider application. We report a twist-stable and hydrophilic coiled CNT yarn produced by the facile electrochemical oxidation (ECO) method. The ECO-treated coiled CNT yarn is prepared by applying low potentiostatic voltages (3.0–4.5 V vs Ag/AgCl) between the coiled CNT yarn and a counter electrode immersed in an electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…29 There are many ways to modify the electrochemical surface area of CNTs, for example, by adding guests with functional groups, 30,31 using small-diameter multiwalled carbon nanotubes (MWCNTs) 32 or facile electrical oxidation of CNT sheets. 33 Somehow, after these processes, the electrical conductivity of CNTs will decrease, which affects the generated output electrical power. Note that a high temperature annealing process is a feasible way to increase the electrical conductivity 34 and mechanical strength 35,36 of CNT yarns, because the structural defects can be healed during the high temperature annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…29 There are many ways to modify the electrochemical surface area of CNTs, for example, by adding guests with functional groups, 30,31 using small-diameter multiwalled carbon nanotubes (MWCNTs) 32 or facile electrical oxidation of CNT sheets. 33 Somehow, after these processes, the electrical conductivity of CNTs will decrease, which affects the generated output electrical power. Note that a high temperature annealing process is a feasible way to increase the electrical conductivity 34 and mechanical strength 35,36 of CNT yarns, because the structural defects can be healed during the high temperature annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs), featuring an excellent combination of low density, superior flexibility, ultrahigh strength and modulus, and good thermal and electrical conductivities, have been well known as the ideal building block for the next-generation high-performance fibers. Owing to these outstanding features, carbon nanotube fibers (CNTFs) could achieve plenty of engineering applications in bulletproof vests, lightweight wires, artificial muscles, energy systems, flexible electronics, etc. Various techniques have been developed to produce CNTFs, such as spinning from the CNT liquid crystal dope, , spinning from the vertically aligned CNT arrays, and direct spinning from the CNT aerogels. Generally, the direct spinning process offers a feasible way to realize the continuous and scalable production of CNTFs. However, so far, the properties of CNTFs, particularly their strength and electrical conductivity, are still not a circumstance to individual CNTs, ,, strongly hindering their niche applications.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, artificial muscle fibers have opened up promising opportunities for preparing more compact and flexible drive units (9)(10)(11)(12)(13)(14)(15). Like natural muscles, artificial muscle fibers provide large and reversible contractile strokes while lifting heavy loads when driven by the stimuli such as heat (9,(15)(16)(17), humidity (18)(19)(20), solvent (17,(21)(22)(23), and doublelayer charging (10,17,24). For example, Haines et al (9) demonstrated that electrothermal nylon 6,6 artificial muscle fibers could achieve a maximum specific work of 2.48 J g −1 and a maximum mechanical output power of 27.1 W g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, artificial muscle fibers have opened up promising opportunities for preparing more compact and flexible drive units ( 9 15 ). Like natural muscles, artificial muscle fibers provide large and reversible contractile strokes while lifting heavy loads when driven by the stimuli such as heat ( 9 , 15 17 ), humidity ( 18 20 ), solvent ( 17 , 21 23 ), and double-layer charging ( 10 , 17 , 24 ). For example, Haines et al.…”
Section: Introductionmentioning
confidence: 99%